2021
DOI: 10.1016/j.rdc.2021.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Nonbacterial Osteomyelitis

Abstract: To review the neuroimaging of a series of infants and young children admitted to hospital with subdural haemorrhage (SDH). Methods: Neuroradiological investigations of 74 children under 2 years of age, from South Wales and southwest England, in whom an SDH or subdural effusion had been diagnosed between 1992 and 2001, were reviewed. Two paediatric neuroradiologists blinded to the original radiological report reviewed all the relevant images. Results: Neuroradiological review of images identified radiological f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 71 publications
0
7
0
Order By: Relevance
“…In recent studies, it was found that functional mutations in MPO, a regulator of neutrophil-associated inflammation in the skin, can induce pustular psoriasis 35 . The common presence of Cutibacterium acnes within bone biopsy samples in adult patients diagnosed with synovitis, acne, pustulosis, hyperostosis, osteitis (SAPHO) syndrome, thought to be a subtype of CNO that occurs mostly in adults, suggested that this bacterial species may be associated with the disease 36 . Combined with the ROC curve results of MPO in this study (AUC = 0.60), this observation gives us reason to believe that MPO plays a specific role in the pathogenesis of CNO.…”
Section: Discussionmentioning
confidence: 99%
“…In recent studies, it was found that functional mutations in MPO, a regulator of neutrophil-associated inflammation in the skin, can induce pustular psoriasis 35 . The common presence of Cutibacterium acnes within bone biopsy samples in adult patients diagnosed with synovitis, acne, pustulosis, hyperostosis, osteitis (SAPHO) syndrome, thought to be a subtype of CNO that occurs mostly in adults, suggested that this bacterial species may be associated with the disease 36 . Combined with the ROC curve results of MPO in this study (AUC = 0.60), this observation gives us reason to believe that MPO plays a specific role in the pathogenesis of CNO.…”
Section: Discussionmentioning
confidence: 99%
“…However, 40-60% of patients do not respond to NSAIDs [24,27,30]. Second-line treatments include csDMARDs, bisphosphonates and TNFi [28,[30][31][32], but it is unclear what is the best second-line medication and among pediatric rheumatologists' practices vary widely [29].…”
Section: Evolution Of Chronic Nonbacterial Osteomyelitis Treatmentmentioning
confidence: 99%
“…Although physical examination is usually normal, tenderness, swelling, or warmth may be present over the affected bones. Along with CNO, other inflammatory conditions affecting various organs can be observed, including severe acne, pyoderma gangrenosum, palmoplantar pustulosis, inflammatory bowel disease, and spondylarthritis [ 2 ]. Imaging studies, especially magnetic resonance imaging (MRI), are crucial in diagnosing and monitoring CNO and determining the numbers and sites of affected bones and responses to treatment [ 3 ].…”
Section: Introductionmentioning
confidence: 99%